Strange hadron production at SIS energies: an update from HADES. (January 2016) - Lorenz, M.; Adamczewski-Musch, J.; Arnold, O.; Atomssa, E.T.; Behnke, C.; Berger-Chen, J.C.; Biernat, J.; Blanco, A.; Blume, C.; Böhmer, M.; Bordalo, P.; Chernenko, S.; et al.
Abstract: We present and discuss recent experimental activities of the HADES collaboration on open and hidden strangeness production close or below the elementary NN threshold. Special emphasis is put on the feed-down from ϕ mesons to antikaons, the presence of the Ξ - excess in cold nuclear matter and the comparison of statistical model rates to elementary p+p data. The implications for the interpretation of heavy-ion data are discussed as well.